Prevalence, anti-malarial chemoprophylaxis and causes of deaths for severe imported malaria: A systematic review and meta-analysis - Mahittikorn A. (2023)
Background: There are limited data regarding prevalence, anti-malarial chemoprophylaxis, and causes of death for severe imported malaria. Thus, we conducted a systematic review and meta-analysis to characterise these variables. Methods: We searched studies reporting deaths attributable to severe imported malaria. The following pooled prevalence rates were determined: 1) the pooled prevalence of severe malaria among patients with imported malaria, 2) the pooled prevalence of deaths among patients with severe imported malaria, 3) the pooled prevalence of anti-malarial chemoprophylaxis among patients with severe imported malaria, and 4) the causes of death among patients with severe imported malaria. Results: The search identified 52 studies that were mainly conducted in Europe (25, 48.1%), North America (16, 30.8%) and Asia (7, 13.5%). The pooled prevalence of severe imported malaria was 12.5% (95% confidence interval [CI] = 10.3%–14.6%, I2 = 99.32%, 12393 severe cases/118325 imported cases). The pooled prevalence of deaths attributable to severe imported malaria was 5.1% (95% CI = 4.0%–6.2%, I2 = 91.72%, 721 deaths/16310 severe cases). The pooled prevalence of adequate anti-malarial chemoprophylaxis among patients with severe imported malaria was 9.7% (95% CI = 6.5%–13.0%, I2 = 89.9%, 203/2049 cases). The most common cause of death was multi-organ failure (12.3%). Conclusion: The results highlighted the need for education and preventative measures for travellers, immigrants, or workers who plan to visit malaria-endemic areas to minimize the risk of severe disease or death.